2016
DOI: 10.1002/pon.4212
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and dementia: an exploratory study of the experience of cancer treatment in people with dementia

Abstract: Objective Patients with comorbid cancer and dementia have poorer outcomes than those without dementia. We observe oncology teams managing patients with dementia and memory loss and explore these patients' needs and experiences of out-patient cancer services. MethodsA single site investigation of case study design to examine practices in four clinics using multi-methods of data collection; retrospective note review, observation, interviews and recorded consultations. A framework analytic approach identifies the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
102
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(106 citation statements)
references
References 20 publications
2
102
0
2
Order By: Relevance
“…Of the six studies included (Table ), five were conducted in the United Kingdom and one in the United States. One study used a quantitative cross sectional design, and five studies used a qualitative design . Two studies explored treatment decision making in the context of hypothetical treatment scenarios, three studies observed prospective treatment decision making in clinical scenarios, and one study interviewed patients and caregivers who were reflecting retrospectively on the cancer diagnosis and treatment decision making …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the six studies included (Table ), five were conducted in the United Kingdom and one in the United States. One study used a quantitative cross sectional design, and five studies used a qualitative design . Two studies explored treatment decision making in the context of hypothetical treatment scenarios, three studies observed prospective treatment decision making in clinical scenarios, and one study interviewed patients and caregivers who were reflecting retrospectively on the cancer diagnosis and treatment decision making …”
Section: Resultsmentioning
confidence: 99%
“…Following screening, clinical investigation, and diagnosis, the initial cancer consultation was often the first point in the cancer treatment pathway where HCPs met with patients and their caregivers to discuss treatment options. Four studies explored the experiences of caregivers and HCPs in the cancer setting through observation of consultations and semi‐structured interviews . Caregivers in one study reflected back on the consultation where the person living with dementia received their cancer diagnosis …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations